A Porcine Model Comparing NRP and Cold Storage versus NRP and Ex-Situ Perfusion in the Distant Procurement of DCD Hearts - Page, A.; Messer, S.; White, P.; Colah, S.; Razzaq, N.; Stathopoulou, T.; Viscasillas, J.; Alibhai, H.; Large, S. (The Journal of heart and lung transplantation, 2019)
Heart donation after circulatory death (DCD) has significantly improved organ utilisation with promising early outcomes. To date, adult DCD heart programmes have relied largely on ex-situ heart perfusion during transport of the donor organs even after normothermic regional perfusion (NRP) in the donor where the heart is formally assessed after circulatory arrest. In this pre-clinical porcine study we compare the use of cold storage as an alternative to ex-situ heart perfusion following NRP. The porcine model of DCD was established with hypoxic arrest after baseline functional measurements were taken including thermo-dilution cardiac studies and pressure-volume loop measurements. Following mechanical asystole a fixed warm ischaemic period was allowed to model for the observation period and the time taken for transfer and access to the heart and major vessels in the clinical setting. NRP was established and the hearts perfused for 60 minutes before being weaned from NRP and functionally assessed. The hearts were then subject to cold storage (CS) with cardioprotective flush or ex-situ heart perfusion (ESHP) for 2 hours. The hearts were then functionally assessed on a left sided working rig with pressure-volume loop measurements. There were 5 animals in the NRP+CS and 6 in the NRP+ESHP groups respectively. All NRP+CS hearts and 5 out of the 6 NRP+ESHP were able to function in working mode for assessment on the rig with the left side loaded to a left atrial pressure of 20mmHg (Table 1). These data suggest that NRP sufficiently resuscitates DCD hearts to allow for cold storage following functional assessment. In the porcine model, ESHP did not appear to offer any added advantage over conventional CS of 2 hours. Further work is required to determine the upper limit of cold ischaemic time that would be tolerated by the DCD heart and we should be cautious in extending CS until we have further information to guide us in the longer usage of CS after NRP.